Revitalisasi asas teknologi sebagai fondasi pengembangan kurikulum PAI di perguruan tinggi era artificial intelligence - Ahmad Choirun Najib; Khalimatus Sa’diyah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the urgency of revitalizing technological principles as the foundation for developing Islamic Religious Education (PAI) curriculum in higher education in the era of Artificial Intelligence. The rapid development of AI demands an adaptive PAI curriculum, but limited understanding of technological principles remains instrumental and partial. This study uses a qualitative approach with a literature review method of relevant scientific articles, books, and documents analyzed descriptively and analytically. The results indicate that revitalizing technological principles needs to be done through repositioning technology as a conceptual framework for curriculum development, not just as a learning tool. These findings emphasize the importance of adaptive, critical, and valuable technology integration so that the PAI curriculum remains academically relevant and morally and spiritually sound. This study has implications for strengthening PAI curriculum development theory, learning practices in higher education, and Islamic education policy. Further research is recommended to examine the empirical implementation of revitalizing technological principles in the context of PAI learning.